2014
DOI: 10.1007/s12274-014-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Restoring pristine Bi2Se3 surfaces with an effective Se decapping process

Abstract: High quality thin films of topological insulators (TI) such as Bi2Se3 have been successfully synthesized by molecular beam epitaxy (MBE). Although the surface of MBE films can be protected by capping with inert materials such as amorphous Se, restoring an atomically clean pristine surface after decapping has never been demonstrated, which prevents in-depth investigations of the intrinsic properties of TI thin films with ex-situ tools.Using high resolution scanning tunneling microscopy/spectroscopy (STM/STS), w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…[9]) we believe that other molecules from atmosphere, most likely water vapor, are the origin of the observed contamination. This conclusion emphasizes that for further ex situ electronic transport investigations and quantum device fabrication, films should first be capped in situ to avoid any possible contamination as has already been indicated for Bi 2 Se 3 thin films [54]. For Bi 2 Te 3 films, though, a systematic study is needed in order to determine a suitable capping layer that can preserve the surface states and avoid unintentional doping induced by ambient conditions.…”
Section: Extrinsic Defectsmentioning
confidence: 90%
“…[9]) we believe that other molecules from atmosphere, most likely water vapor, are the origin of the observed contamination. This conclusion emphasizes that for further ex situ electronic transport investigations and quantum device fabrication, films should first be capped in situ to avoid any possible contamination as has already been indicated for Bi 2 Se 3 thin films [54]. For Bi 2 Te 3 films, though, a systematic study is needed in order to determine a suitable capping layer that can preserve the surface states and avoid unintentional doping induced by ambient conditions.…”
Section: Extrinsic Defectsmentioning
confidence: 90%
“…The samples were first sputtered with 500 eV argon ions for 15 minutes. Subsequently, they were annealed up to ~200 °C to desorb the amorphous Se, after which they were immediately transferred into the STM head for measurements 40 . …”
Section: Stm Measurementsmentioning
confidence: 99%
“…Se capping is preferably used due to its low desorption temperature, but it normally changes the surface stoichiometry of Te-based TI compounds during thermal decapping. 18,19 Refinements of this technique have shown that it is possible to restore pristine surfaces after thermal removal of sputtered Se capping on Bi 2 Se 3 , which was exposed to air for a few hours 20 or thermal desorption of ultra-thin Te capping on Bi 2 Te 3 films after exposition to air for 5 min. 21 A third technique applied to layered van der Waals materials consists of cleaving thin films (thicker than 50 nm) inside the UHV chamber to remove the oxidized surface, exposing a new fresh surface to perform the aimed analysis.…”
mentioning
confidence: 99%